The Comparison of Differentially Expressed microRNAs in Bag-1 Deficient and Wild Type MCF-7 Breast Cancer Cells by Small RNA Sequencing - KILBAŞ, PELİN ÖZFİLİZ; Alkurt, Gizem; Çoker Gürkan, Ajda; DİNLER DOĞANAY, GİZEM; ARISAN, ELİF DAMLA; YERLİKAYA, PINAR OBAKAN (TUBITAK Scientific & Technical Research Council Turkey, 2022)
The multifunctional BAG-1 (Bcl-2 athanogene-1) protein promotes breast cancer survival through direct or indirect interaction partners. The number of the interacting partners determines its cellular role in different conditions. As well as interaction partner variability, the amount of BAG-1 protein in the cells could cause dramatic alterations. According to previous studies, while the transient silencing of Bag-1 enhanced drug-induced apoptosis, deletion of BAG-1 could induce stemness properties and Akt-mediated actin remodeling in MCF-7 breast cancer cells. Considering the heterogeneity of breast cancer and the variability of BAG-1-mediated cell response, it has become essential to determine microRNA (miRNA) functions in breast cancer depending on Bag-1 expression level. This study aims to compare microRNA expression levels in wt and Bag-1 knockout (KO) MCF-7 breast cancer cells. hsa-miR-429 was selected as a potential miRNA in BAG-1KO MCF-7 cells because of the downregulation both in bioinformatics and validation qRT-PCR assay. According to predicted mRNA targets and functional enrichment analysis the ten hub proteins that are phosphatidylinositol4,5-biphosphate 3-kinase catalytic subunit alpha (PIK3CA), kinase insert domain receptor (KDR), GRB2 associated binding protein 1 (GAB1), Rac family small GTPase1 (RAC1), vascular endothelial growth factor A (VEGFA), Cbl proto-oncogene (CBL), syndecan 2 (SDC2), phospholipase C gamma 1 (PLCG1), E1A binding protein p300 (EP300), and CRK like proto-oncogene, adaptor protein (CRKL) were identified as targets of hsa-miR-429. The functional enrichment analysis showed that the most significant proteins were enriched in PI3K/Akt, focal adhesion, cytoskeleton regulation, proteoglycans in cancer, and Ras signaling pathways. It was determined that hsa-miR-429 targeted these pathways in Bag-1 deficient conditions and could be used as a potential therapeutic target in future studies.
Keywords: Bag-1 Knockout; Small RNA Sequencing; miRNA; hsa-miR-429; MCF-7; Breast Cancer